Electric field distribution on porcelain-type insulator under corona discharge - Ho, Kian Tsong (2018)
Porcelain insulator is widely used in high voltage transmission due to its high stability and long service track record. However, despite the advantage, outdoor service insulator string is exposed to service conditions that lead to electrical discharge risk such as corona discharge. The side effect of corona discharge is difficult to mitigate and will degrade the performance of the insulator string. This project investigates the behaviour of corona discharge using laboratory test and computer simulation (ANSYS Maxwell-2D). Porcelain insulator unit was injected with AC voltage to study the behaviour of corona discharge on the insulator surface. Next, the result of the laboratory test was used in the simulation to visualise the electric field distribution around the porcelain insulator unit. As for a mitigation approach, corona ring is simulated with the insulator model and the electric field and voltage across insulator are obtained. The result of electric field on porcelain insulator surface applied with different condition was compared with and without corona ring. An optimisation of the corona ring parameter was also carried out by taking into account its effect on the electric field and voltage distribution. It is found that corona discharge occurs easily on the intersection part of porcelain insulator cap and porcelain insulator shell. In addition to that, it is found from the simulation that the electric field at the intersection of the porcelain insulator cap and porcelain insulator shell corona ring is about 63 kVcm-1 whilst the electric field at the edge of the insulator surface is only 3 kVcm-1. The electric field at the intersection of the insulator cap and porcelain insulator shell even higher when insulator surface condition such as coating and water droplet are considered. Furthermore, simulation showed that by adding the corona ring to the porcelain insulator string, the electric field on the insulator surface reduced to lower level as opposed to the one without the corona ring. At some point of interests, other results suggested that the corona ring able to reduce the electric field up to 34% and variations in dimensioning the corona ring also indicated significant effect in changing the electric field distribution on the insulator.